Examination of the effect of spinal anesthesia informational video on anxiety level and postoperative analgesia in transurethral resection of prostate - Bezen, Bilal Atilla; Taşkapılı, Kamil; Yazar, Veli Mert; Gerçek, Osman; Eren, Berkay (Frontiers in Medicine, 2025)
ObjectivesTo evaluate the effect of an informational video on spinal anesthesia in reducing preoperative anxiety and postoperative analgesic requirements in patients undergoing TURP surgery.Materials and methodsThis clinical trial was conducted on 93 urologic patients, who underwent transurethral resection of prostate with spinal anesthesia. The patients were randomly divided into two groups using a website: Group 1 who received informational video about spinal anesthesia at least 2 h before the operation in addition to standard verbal and written information, Group 2 who received standard verbal and written information. The baseline anxiety levels of all patients were evaluated in the preoperative anesthesia outpatient clinic (T0). A second time, anxiety levels were measured in the preoperative preparation room (T1). Intraoperative sedation levels were monitored with an OAASS score of 3–4. The amount of the additional dexmedetomidine administered was recorded. Postoperative 0th, 2nd, 4th, 6th, 12th, and 24th hour VAS scores and the rescue analgesic time and amount were recorded.ResultsNo significant difference was found between the groups in terms of STAI-T, STAI-S0, APAIS-Anxiety0, APAIS-Information0 measured in the preoperative outpatient clinic evaluation (p > 0.05). STAI-S1, APAIS-Anxiety1, and APAIS-Information1 results assessed in the preoperative preparation room were found to be significantly lower in Group 1 (p = 0.001, for each). When the median amount of additional dexmedetomidine per kilogram was compared, 0.10 μg/kg (IQR: 0.09) were used in Group-1, while 0.30 μg/kg (IQR: 0.17) were used in Group-2. Intraoperative additional dexmedetomidine requirement was significantly lower in Group 1 (p = 0.001). Although the amount and timing of rescue analgesic use did not differ between the groups, the proportion of patients requiring rescue analgesia within 24 h was significantly lower in Group 1 (p = 0.284, p = 0.926, p = 0.033, respectively).ConclusionIn the preoperative period, the spinal anesthesia information video reduces preoperative anxiety more than standard verbal and written information. Additionally, the spinal anesthesia information video also reduces the amount of sedative agents used intraoperatively.